The Use of Scattergories Game to Develop Students’ Vocabulary Mastery - Kartika, Niluh Yuni; Rofiqoh, Rofiqoh; Lebagi, Desrin; Mukrim, Mukrim (Universitas Pahlawan Tuanku Tambusai, 2025)
Scattergories game is a version of the category game that promotes broad word acquisition. This research aims to prove whether the use of the Scattergories game can develop vocabulary mastery of the seventh-grade students at SMP Negeri 1 Parigi. This research used a quasi-experimental design involving two groups: experimental and control groups. The population consisted of five seventh-grade classes. The test was administered twice as a pre-test and post-test to assess students’ vocabulary mastery before and after the treatment. Because the data were not normally distributed, the data were analyzed using the Mann-Whitney U test through SPSS version 24. This finding showed a difference in mean scores post-test of the control and experimental groups, where the mean scores of the control group were 78 and the experimental group were 85. The Mann-Whitney test showed that there was a significant increase in the experimental classes (Z = -1.975, p = 0.048). This result suggests that the Scattergories game effectively enhances vocabulary mastery of the seventh-grade students, making the learning process more engaging and impactful.